Manajemen Pengelolaan Karya Guru dan Siswa Melalui Gerakan Literasi di Sekolah Penggerak SMP Bilingual Terpadu Junwangi Krian Sidoarjo - Sa’idah Kusmiyanti; Ashari Ashari (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2023)
This study use a qualitative approach with the type of case study in Sekolah Penggerak SMP Bilingual Terpadu Junwangi Krian Sidoarjo. As for the data collection tehniques, used observation,interview and documentation tehniques. The stages in the data analysis use the stage of condensing data analysis,data presentation, and drawing conclusions. Meanwhile, checking the validity the data is through. Participation extensions source triangulation and technical triangulation. The result of this study are 1) The teaching materials LKPD (Lembar Kerja Peserta Didik) name’s ‘Alima arranged by crew MGMPS,The books have ISBN from self publish of institution “Bendera Al Amanah Pers”, review, poetry, anthology, class mading and outdoor mading; 2) The education report, design budget of school, build the literacy organizational structure ,meeting literacy team and MGMPS Indonesia teacher and the literacy cost; 3) Organizing with literacy organization structure,The coordinator has responsibility wih headmaster’ SK,The communication with students of OSIS; 4) The implicationts are giving facility in the library or out library, the student must visit library and give a present to active student,the school have library car,ISBN’s book Publish’Bendera Al Amanah Pers’and overseas book,the class mading,MGMPS mading,race in the school and outside,assessment team,daily literacy,monthly literacy,yearly literacy,start a bookfair,education repot of teacher and rew 5) ard; The evaluations with education instrument of national assessment and evaluation with intern meeting and big meeting.